Effect of light-touch intervention and associated factors to microbial contamination at small-scale pig slaughterhouses and traditional pork shops in Vietnam - Hai Hoang Tuan Ngo; Sinh Dang-Xuan; Målqvist, M.; Luong Nguyen-Thanh; Phuc Pham-Duc; Phi Nguyen-Hong; Hang Le-Thi; Hung Nguyen-Viet; Trang Thi-Huyen Le; Grace, Delia; Lindahl, Johanna F.; Unger, Fred (Elsevier, 2023)
Traditional pork value chains dominate the production and distribution of pork in Vietnam; however, the high level of microbiological contamination in pork may increase the risk of food-borne disease for consumers. There is limited evidence about how to feasibly and scalably reduce microbial contamination in pork sold in traditional markets. This study aimed to assess the effectiveness of light-touch interventions for changing worker behaviour in small-scale slaughterhouses and vendors at traditional pork shops, as well as to identify risk factors for pork contamination. The intervention packages consisted of providing hygiene tools and delivering a food safety training which had been designed in a participatory way and covered 10 small-scale slaughterhouses and 29 pork shops. Pig carcasses, retailed pork, contact surfaces, and hands were sampled to measure the total bacterial count (TBC) and Salmonella contamination before, three and six weeks after the intervention, and trainee practices were observed at the same time. Linear and generalized linear mixed effects models were constructed to identify risk factors for TBC and Salmonella contamination at the slaughterhouses and pork shops. The interventions at slaughterhouses and pork shops both showed a slight reduction of TBC contamination in pig carcasses and Salmonella prevalence in retailed pork, while the TBC in retailed pork decreased only marginally. For slaughterhouses, the regression model indicated that smoking or eating during slaughtering (indicating poor hygienic practices) was associated with TBC increasing, while cleaning floors and wearing boots reduced TBC contamination. For pork shops, using rough materials (cardboard or wood) to display pork was the only factor increasing TBC contamination in pork, whereas cleaning knives was associated with lower TBC. Besides, the presence of supporters and wearing aprons reduced the probability of Salmonella contamination in pork. The findings highlight the effectiveness of light-touch interventions in reducing microbial contamination in pig carcasses at small-scale slaughterhouses and pork at traditional shops over the study period.